Neck circumference as an indicator of obesity for Metabolic Syndrome in Mexican Healthcare workers - GONZÁLEZ JAIMES, Norma Lilia; ANDRADE ALMARÁZ, Verónica; MEZA SEGURA, Rodrigo (Nutrición Clínica y Dietética Hospitalaria, 2023)
Background: Neck circumference (NC) is a novel anthropometric indicator to assess adiposity in the cervical region that is rarely used in Mexico. The greatest advantage of this evaluation is the saving of time, minimal use of instruments, and no prerequisites for patients. Objective: This study aimed to determine the effectiveness of NC as an indicator of obesity for Metabolic Syndrome (MetS) in comparison with BMI and Waist Circumference (WC), and to define NC cutoff levels based on parameters established by the International Diabetes Federation in a group of healthcare workers from a Public Health Hospital of the State of Morelos, Mexico. Methods: This was a no-randomized, cross-sectional-observational study. Instruments: Anthropometric evaluation and biochemical parameters: lipid profile, fasting glucose, and blood pressure. Statistical analysis: Descriptive, correlational, Poisson multiple regression adjusted by age/sex, and ROC curves using SPSS.23 program. Results: 200 healthcare workers were recruited (146 women and 54 men), age ẋ=42.87, σ=11.25 years. The prevalence of MetS was 38% (37% in women and 40.7% in men). BMI, WC, and NC were significantly correlated: BMI and WC (r=.924), BMI and NC (r=.814), and NC and WC (r=.810) (p=.01). Likewise, they were related to hyperglycemia, hypertriglyceridemia, hypertension, and decreased in HDL-cholesterol levels. The NC best cut-off points coupled with two or more components of MetS in women was >35.12 cm [AUC=0.765 (95% CI, 0.688-0.843)] and in men >41.25 cm [AUC=0.787 (95% CI, 0.688-0.906)]. Conclusion: NC proved to be a reliable indicator that can be quickly and inexpensively evaluated for the determination of obesity for the preliminary diagnosis of MetS. Keywords: Neck circumference, Cut-off points, Metabolic Syndrome, and Mexican Healthcare workers